Slurry for improving wetting efficiency of hydrophobic catalyst and preparation method thereof

By using shear cans and ultrasonics in the preparation of catalyst slurry, combined with specific dispersants, the problem of difficult hydrophobic catalysts is solved, the wetting efficiency and membrane electrode performance are improved, and the production risk and catalyst deactivation are reduced. .

CN119186356APending Publication Date: 2024-12-27TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411450332.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the batch preparation of catalyst slurry, the hydrophobic catalyst is difficult to wet, resulting in production safety hazards and catalyst deactivation problems.

Method used

By mixing the catalyst with water at low speed in a shearing tank, adding ionomers and alcohols, and processing under ultrasonic and high-pressure homogenizers, a high solids catalyst slurry is prepared, using specific dispersants such as D79. Silicone sol and alkylphenol polyoxyethylene ether, adjust the vacuum degree and temperature to improve wetting efficiency.

Benefits of technology

It significantly improves the wetting properties of water to hydrophobic powder, reduces the use of wetting agents and dispersants, enhances the fluidity of the slurry and the polarization performance of the membrane electrode, reduces safety hazards and catalyst deactivation, and improves the production. Slurry efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186356A_ABST
    Figure CN119186356A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of slurry for improving wetting efficiency of a hydrophobic catalyst, and the preparation method specifically comprises the following steps: uniformly stirring a catalyst, water and a dispersing agent in a shearing tank at a low speed, and adjusting the vacuum degree in the shearing tank to obtain a mixture; and under low-speed stirring, firstly adding the ionomer into the mixture, then adding the alcohol, carrying out ultrasonic treatment until particles are crushed, and then transferring into a high-pressure homogenizer for uniform emulsification to obtain the catalyst slurry with high solid content. Compared with the prior art, air among catalyst particles is efficiently and rapidly removed, the wettability of water to hydrophobic powder is greatly improved, the usage amount of a wetting agent and a dispersing agent is reduced, and the safener production risk existing in large-scale preparation of catalyst slurry is eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Technology

[0002] The present invention relates to the technical field of catalyst slurry preparation, and in particular to a slurry for improving the wetting efficiency of a hydrophobic catalyst and a preparation method thereof. Background Art

[0003] In the batch production process of the catalyst layer, the corresponding catalyst slurry needs to be prepared. Taking the preparation process of low-solid content catalyst slurry of the spraying process as an example, it is customary in the prior art to first mix the ionomer with organic solvents such as water and alcohols to prepare an ionomer dispersion; then, the ionomer dispersion is added to the catalyst powder, and a uniform slurry is prepared by ultrasound, emulsification, etc. However, when facing the batch preparation process of the catalyst layer, tens to hundreds, or even several kilograms of catalyst dry powder need to be mixed with the ionomer and the solvent. In the actual mixing process, the catalytic Pt particles will react chemically with the alcohol molecules present in the ionomer and the solvent in the air, causing the catalyst and the alcohol to burn. This not only poses a safety hazard to production, but also causes the catalyst to lose its catalytic ability and cause production losses.

[0004] The solid content of the catalyst in the catalyst slurry for direct coating process is generally between 6 and 12 wt.%, and the total solid content is between 10 and 20 wt.%. In the process of homogenizing the material, the catalyst (active component / carbon carrier) must be evenly mixed with the ionomer and solvent. The general way of adding materials is to first wet the catalyst particles with water, and then add the ionomer solution and alcohol solvent. However, due to the strong hydrophobicity of the carbon carrier surface and the presence of a large number of polar functional groups on the carbon surface, it is difficult for water molecules to invade the mesopores of the carbon carrier. At the same time, the hydrogen bonding between the polar functional groups and the water molecules causes the slurry to form a large number of uneven flocculation results, which wraps a large amount of solvent, thereby reducing the wettability of water to the catalyst.

[0005] The ionomer acts as a dispersant in the catalyst slurry. The sulfonate groups (R-SO3H) on its surface carry negatively charged groups (R-SO3 - ) to disperse the catalyst particles. However, during the initial mixing process, the ionomer is often not added to the catalyst at the first time, in order to avoid the catalyst from reacting with the alcohols in the ionomer.

[0006] Therefore, there is an urgent need to develop a method for preparing a catalyst slurry that can quickly wet the catalyst and eliminate the safety and production risks in the batch slurry preparation process. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a slurry and a preparation method thereof for improving the wetting efficiency of hydrophobic catalysts. Through a simple preparation method, the air between the catalyst particles can be efficiently and quickly removed, so that the wettability of water to the hydrophobic powder is greatly improved, and the use of wetting agents and dispersants is reduced, thereby eliminating the production risks of safety agents in the large-scale preparation of catalyst slurries.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] The present invention provides a method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst, comprising the following steps:

[0010] S1: stirring the catalyst, water and dispersant uniformly at a low speed in a shear tank, and adjusting the vacuum degree in the shear tank to obtain a mixture;

[0011] S2: Under low-speed stirring, first add the ionomer and then the alcohol to the mixture in S1, and perform ultrasonication until the particles are broken. Then transfer the mixture to a high-pressure homogenizer for uniform emulsification to obtain a catalyst slurry with a high solid content.

[0012] Furthermore, in S1, the vacuum degree in the shear tank is less than 0.1 MPa, and the temperature in the shear tank is -5°C to 20°C.

[0013] Further, in S1, the added volume of water is greater than the added volume of the catalyst, and the added volume of the catalyst satisfies:

[0014] The volume of the catalyst V2 = the mass of the catalyst M2 × the carbon mass fraction / the apparent density of carbon ρ2.

[0015] Furthermore, in S1, the dispersant includes one of D79, silica sol, alkylphenol polyoxyethylene ether, and sodium octyl sulfate (Proof-08).

[0016] Furthermore, the mass ratio of the dispersant to the catalyst is 0.05-0.5.

[0017] Furthermore, the homogenizing pressure of the high-pressure homogenizer is 20-30 MPa, and the operating frequency of the plunger in the high-pressure homogenizer is greater than or equal to 40 Hz.

[0018] Furthermore, in S2, an ultrasonic probe is used for ultrasound, the power of the ultrasonic probe is less than or equal to 120 W, and the ultrasound time is greater than 1 hour.

[0019] Furthermore, in S1 and S2, the speed of the low-speed stirring is less than 2000 RPM.

[0020] Furthermore, in S1 and S2, the addition amount of the ionomer and the catalyst satisfies:

[0021] The mass of the ionomer / the mass of the catalyst M2×the carbon mass fraction=0.3~1.5.

[0022] The present invention also provides a slurry for improving the wetting efficiency of a hydrophobic catalyst.

[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0024] 1. The present invention efficiently and quickly removes the air between the catalyst particles, greatly improves the wettability of water to the hydrophobic powder, reduces the amount of wetting agent and dispersant used, and eliminates the risk of safety agent production in large-scale preparation of catalyst slurry.

[0025] 2. The use of dispersants in the present invention can significantly reduce the average particle size of catalyst agglomerate particles, and significantly increase the fluidity of the slurry, thereby increasing the wetting efficiency. When the wetting efficiency is increased, the reaction between Pt particles and alcohol molecules is greatly suppressed, thereby improving the polarization performance of the membrane electrode. In addition, the pulping efficiency of the present invention is 12 to 20 mL / min, which is 2 to 4 times higher than the pulping efficiency, eliminating safety hazards and avoiding the deactivation of precious metals. The preparation method is simple and is suitable for the preparation of high solid content catalyst slurries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a comparison chart of the average particle sizes of the catalyst / water mixtures obtained in Comparative Example 1, Example 1, Example 2, and Example 3;

[0027] Figure 2 is the viscosity @100s of the catalyst / water mixture obtained in Comparative Example 1, Example 1, Example 2 and Example 3 -1 Comparison chart;

[0028] Figure 3 It is a comparison chart of the polarization curves of the catalyst slurries obtained in Comparative Example 1, Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0029] The specific implementation methods of the present invention are described in detail below through examples. These examples are implemented on the premise of the scheme described in the present invention, and provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to the following examples.

[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Any features such as component models, material names, connection structures, preparation methods, materials, structures or composition ratios not clearly described in this technical solution are deemed to be common technical features disclosed in the prior art.

[0031] Example 1

[0032] This embodiment provides a method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst, comprising the following steps:

[0033] S1: Pour 80g of 50wt.% Pt / C catalyst powder into a shear tank, add 197.2g of deionized water, and then add 4g of D79 dispersion. Use a vacuum pump to adjust the vacuum degree in the shear tank to 0.09MPa, stir at a low speed for 10min at a rotation speed of 1800RPM to obtain a catalyst / water mixture.

[0034] S2: 140 g of perfluorosulfonic acid ionomer (D2020, Nafion 20 wt.%) and 302.8 g of ethanol were added to the catalyst / water mixture obtained in S1 in sequence. An ultrasonic probe with an ultrasonic power of 120 W was used, the ultrasonic time was 1.5 h, the ultrasonic temperature was 10° C., and the slurry was dispersed by a high-pressure homogenizer, the homogenization temperature was -5° C., the homogenization pressure was 200 bar, the plunger frequency in the high-pressure homogenizer was 40 Hz, and the homogenization dispersion times were 5 times to obtain a catalyst slurry, and a membrane electrode (MEA) was prepared for testing.

[0035] The particle size and viscosity of the catalyst / water mixture prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were tested using a nanoparticle size analyzer and a rotational rheometer. Figure 1 and Figure 2 As shown in the figure, it can be seen that the addition of dispersant significantly reduces the particle diameter of the catalyst / water mixture, and the particle diameter is reduced from several microns to hundreds of nanometers; in comparison, D79 has the strongest wetting and dispersion effect on the particles in the mixture, followed by alkylphenol polyoxyethylene ether, and silica sol is the worst. At the same time, the viscosity is significantly reduced and the fluidity is significantly enhanced. The reduction of particle size and the enhancement of fluidity can greatly increase the laminar flow rate of the fluid at the same power, reduce the dispersion time, and improve the pulping efficiency.

[0036] Figure 3 is the polarization curve diagram of the catalyst slurry obtained in each embodiment and comparative example, Figure 3 It can be seen that alkylphenol polyoxyethylene ether and silica sol do not have proton conductivity, so they have no obvious effect on improving the performance of the membrane electrode; while D79 itself has proton conductivity. At the same time, the preparation method in this embodiment effectively wets the catalyst surface to avoid active deactivation. Therefore, the polarization performance of the membrane electrode is significantly increased.

[0037] Example 2

[0038] This embodiment provides a method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst, comprising the following steps:

[0039] S1: Pour 80g of 50wt.% Pt / C catalyst powder into a shear tank, add 197.2g of deionized water, and then add 4g of silica sol dispersion. Use a vacuum pump to adjust the vacuum degree to 0.09MPa, stir at a low speed for 10min, and the rotation speed is 1800RPM to obtain a catalyst / water mixture.

[0040] S2: 140 g of D2020 and 302.8 g of ethanol were added to the catalyst / water mixture obtained in S1. An ultrasonic probe with an ultrasonic power of 120 W was used, the ultrasonic time was 1.5 h, and the ultrasonic temperature was 10°C; the slurry was dispersed by a high-pressure homogenizer, the homogenization temperature was -5°C, the homogenization pressure was 200 bar, the plunger frequency in the high-pressure homogenizer was 40 Hz, and the homogenization dispersion times were 5 times to obtain a catalyst slurry, which was prepared into MEA for testing.

[0041] Example 3

[0042] This embodiment provides a method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst, comprising the following steps:

[0043] S1: Pour 80g of 50wt.% Pt / C catalyst powder into a shear tank, add 197.2g of deionized water, and then add 4g of alkylphenol polyoxyethylene ether. Use a vacuum pump to adjust the vacuum degree to 0.09MPa, stir at a low speed for 10min, and obtain a catalyst / water mixture.

[0044] S2: 140 g of D2020 and 302.8 g of ethanol were added to the catalyst / water mixture obtained in S1. An ultrasonic probe with an ultrasonic power of 120 W was used, the ultrasonic time was 1.5 h, and the ultrasonic temperature was 10°C; the slurry was dispersed by a high-pressure homogenizer, the homogenization temperature was -5°C, the homogenization pressure was 200 bar, the plunger frequency of the high-pressure homogenizer was 40 Hz, and the homogenization dispersion times were 5 times to obtain a catalyst slurry, which was prepared into MEA for testing.

[0045] Comparative Example 1

[0046] This comparative example provides a method for preparing a catalyst slurry, comprising the following steps:

[0047] S1: Pour 80 g of 50 wt.% Pt / C catalyst powder into a shear tank, add 197.2 g of deionized water, use a vacuum pump to adjust the vacuum degree to 0.09 MPa, stir at a low speed for 10 min at a rotation speed of 1800 RPM to obtain a catalyst / water mixture.

[0048] S2: 140 g of D2020 and 302.8 g of ethanol were added to the catalyst / water mixture obtained in S1 in sequence. The ultrasonic power was 120 W, the ultrasonic time was 1.5 h, and the ultrasonic temperature was 10°C; the catalyst slurry was then dispersed using a homogenizer, the homogenization temperature was -5°C, the homogenization pressure was 200 bar, the plunger frequency was 40 Hz, and the homogenization dispersion times were 5 times to obtain the catalyst slurry, which was then prepared into MEA for testing.

[0049] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst, characterized in that: The following steps are involved: S1: stirring the catalyst, water and dispersant uniformly at a low speed in a shear tank, and adjusting the vacuum degree in the shear tank to obtain a mixture; S2: Under low-speed stirring, first add the ionomer and then the alcohol to the mixture in S1, and perform ultrasonication until the particles are broken. Then transfer the mixture to a high-pressure homogenizer for uniform emulsification to obtain a catalyst slurry with a high solid content.

2. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S1, the vacuum degree in the shear tank is less than 0.1 MPa, and the temperature in the shear tank is -5°C to 20°C.

3. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S1, the added volume of water is greater than the added volume of the catalyst, and the added volume of the catalyst satisfies: The volume of the catalyst V2 = the mass of the catalyst M2 × the carbon mass fraction / the apparent density of carbon ρ2.

4. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S1, the dispersant includes one of perfluorosulfonic acid ionomer (D79), silica sol, alkylphenol polyoxyethylene ether, and sodium octyl sulfate.

5. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: The mass ratio of the dispersant to the catalyst is 0.05-0.

5.

6. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: The homogenizing pressure of the high-pressure homogenizer is 20-30 MPa, and the operating frequency of the plunger in the high-pressure homogenizer is greater than or equal to 40 Hz.

7. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S2, an ultrasonic probe is used for ultrasound, the power of the ultrasonic probe is less than or equal to 120 W, and the ultrasound time is greater than 1 hour.

8. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S1 and S2, the speed of the low-speed stirring is less than 2000 RPM.

9. The method for preparing a slurry for improving the wetting efficiency of a hydrophobic catalyst according to claim 1, characterized in that: In S1 and S2, the addition amount between the ionomer and the catalyst satisfies: The mass of the ionomer / the mass of the catalyst M2×the carbon mass fraction=0.3~1.

5.

10. A slurry for improving the wetting efficiency of a hydrophobic catalyst obtained by the preparation method according to any one of claims 1 to 9.